FUNCTIONALIZATION OF PARKIA BIGLOBOSA MEDIATED-GOLD NANOPARTICLE FOR IMPROVED DRUG DELIVERY - Okoampah, E.; Davids, J. S.; Payne, J. (UDS International Journal of Development, 2023)
NPs have emerged as promising in the pharmaceutical industry, prompting several studies into their potential as drug delivery agents due to their biocompatibility with cellular structures. Antibiotic resistance has increased over time, as has the unrealistic bio-distribution of antibiotics to disease sites, making it critical to improve antibiotic efficiency in order to cure disease. This study investigated the bio-reduction and stability potential of HAuCl4 by obtaining gold nanoparticles (AuNPs) from the leaves of Parkia biglobosa and studying their drug release potential using three nanodrug composites, PD (PEG conjugated on lincomycin), PN (PEG conjugated on AuNPs), and PND (PEG conjugated on AuNPs) (PEG and lincomycin on AuNPs). UV-Vis spectrophotometry, TEM, FTIR, XRD, and EDS were used to characterize the as-synthesized AuNPs and the formulated nanodrug composites. For all three drug composites, an optimal released capacity was reached at 9 minutes after an initial drug release capacity at 3 minutes for PD, PN, and PND. PND had a release capacity of 23mg/ml, followed by PD and PN with 12mg/ml and 4.8mg/ ml, respectively. The high drug release capacity observed in the PND composite was due to the AuNPs’ biocompatibility and the ability of PEG to prevent degradation. The antimicrobial activity of the formulated drug composites were able to inhibit the growth of the microbes with PND inhibiting the growth of Pseudomonas aeruginosa, Enterococcus faecalis, Staphylococcus aureus, and Escherichia coli at 43.25mm, 20.25mm, 33.00mm, and 28.00, respectively; followed by PD with the zones of inhibition at 41.75mm, 19.00mm, 30.75mm, and 23.50mm, respectively. PND and PN both inhibited Candida albicans with zones of inhibition of 50.31mm and 49.34mm, respectively. Interestingly, PN had no zone of inhibition on the microbes or fungi. The combined drug release potential and microbial growth inhibition of the as- synthesized formulated drugs provides a new generation technology to improve disease treatment capacity of pharmaceutical drugs. Keywords: Gold Nanoparticles; Antibiotics; Drug Release; Microbes; Polymer